Development of Android Application-Based Learning Media Using Smart Apps Creator (SAC) on Cell Division Materials - Rinaldi, Rinaldi; Hasan, Ani M.; Ibrahim, Mustamin (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Mobile phones are not only used as a communication tool in the millennial era, but they can also be used in the learning process. Mobile phones are rarely used as a learning tool by students. This study aims to determine the validity level of learning media based on Android applications using Smart Apps Creator (SAC) on mitotic and meiotic cell division material. This type of research is research development, or research and development (R&D), using the ADDIE model, which is modified only up to the development stage with limited trials in class XII IPA 1, SMA Negeri 1, Tapa. The results showed that the results of validating learning media based on android applications using Smart Apps Creator (SAC) on mitotic and meiotic cell division material were included in the "very valid" category with a percentage of 3.93%